Cannabis and its dilemmas in psychiatry - Facco, Vinicius Broilo; Rodrigues, Fernando Gabriel; Castel, Giulia Maria Dal; Campos, Larissa Ferreira; Cas, Martina Estacia da; Dariz, Pedro Henrique Sarmento; Escobar, Jefferson José Rodrigues (Seven Editora, 2023)
In the 1960s, the two main chemical structures in the Cannabis plant were isolated: delta-9-tetrahydrocannabinol (Δ9 -THC), a psychotropic component of the plant, and cannabidiol (CBD), a non-psychotropic substance with therapeutic potential. The possible use as a medicine is justified by the wide distribution of cannabinoid receptors in the body. There is still no consensus on the use of CBD in the treatment of psychiatric conditions, as the implementation of this new therapy has been controversial. The Brazilian Association of Psychiatry (ABP) was irremediably against its use, despite some studies reporting benefits. DOI:https://doi.org/10.56238/alookdevelopv1-022